Juridical Review of Default on the Letter Recognition of Debt with Collateral Motor Vehicle (Study of Decision Number 35/Pdt.G/2021/PN. CBN) - Mustafa, Mustafa (Riwayat: Educational Journal of History and Humanities, 2025)
Agreement is the source of an engagement. One of the irregularities in the agreement is breach of contract. In order to provide certainty in an agreement, a guarantee can be held and a letter of acknowledgment of debt can be made. This study is aimed to analyze legal settlements in breach of contract and position of vehicle on bail in Cirebon City District Court Decision Number: 35/Pdt.G/2021/PN. CBN. The method used in this research is normative juridical with prescriptive research specifications. Data source used is secondary data consisting of primary, secondary and tertiary legal materials. Data collected was carried out by literature study, data obtained was presented with narrative text, and the data analysis method used was a qualitative normative method. Based on the results of the research, it can be concluded that a deed of debt recognition can be used for a lawsuit in a court if there is a party that neglects the obligations and can create a rights for creditors in compensation for losses caused by breach of contract. Objects that are controlled by another person but juridically owned by another party, that party has full rights over the object so that the object can be used as an on bail object.